The genus Hoplandrothrips and its relatives (Thysanoptera: Phlaeothripidae) from Southeast Asia and Taiwan - Okajima, Shûji; Masumoto, Masami (Zootaxa, 2024)
Three fungus-feeding phlaeothripine genera included in the Phlaeothrips-lineage, Ecacanthothrips, Hoplandrothrips and Phlaeothrips, are studied taxonomically from Southeast Asia and Taiwan. Ten Ecacanthothrips species are recognised, in which one species is newly described from Bali Is., Indonesia: E. brevicornis sp. n. Seventeen Hoplandrothrips species are recognised, of which 13 species are newly described from Southeast Asia and Taiwan, and one newly recorded species is transferred from Tylothrips: H. adoraneoides sp. n., H. aseanae sp. n., H. asianus sp. n., H. basantratus sp. n., H. coloratus Okajima, H. flavicornis sp. n., H. flavus Bagnall, H. floresi sp. n., H. formosae sp. n., H. graminicola, sp. n., H. laurencei sp. n., H. obesametae Chen, H. quinqueconus sp. n., H. samirseni (Varatharajan, Singh & Bala) comb. n., H. sapae sp. n., H. sulawesi sp. n. and H. thailandicus sp. n. Two Phlaeothrips species are newly described from northern Vietnam: P. annamensis sp. n. and P. tonkinensis sp. n. One African species transferred to Hoplandrothrips from Malacothrips: H. natalensis (Trybom) comb. n. The generic definitions and relationships of these three genera together with Malacothrips are discussed. Three illustrated keys are provided for 12 Ecacanthothrips species, 17 Hoplandrothrips species from Southeast Asia and Taiwan, and two Phlaeothrips species from Vietnam.